DYNAMICS AT INFINITY of A CUBIC CHUA'S SYSTEM - Messias, Marcelo [UNESP] (World Scientific Publ Co Pte Ltd, 2011)
We use the Poincare compactification for a polynomial vector field in R(3) to study the dynamics near and at infinity of the classical Chua's system with a cubic nonlinearity. We give a complete description of the phase portrait of this system at infinity, which is identified with the sphere S(2) in R(3) after compactification, and perform a numerical study on how the solutions reach infinity, depending on the parameter values. With this global study we intend to give a contribution in the understanding of this well known and extensively studied complex three-dimensional dynamical system.
Keywords: Chua's system; Poincare compactification; dynamics at infinity; global behavior; chaotic attractor